Tau Accumulation in the Entorhinal Cortex and Precuneus is Associated with Cortical Amyloid-Beta Burden, Age and Worse Memory Performance in Preclinical Autosomal Dominant Alzheimer's Disease (2018)
Background: We have characterized amyloid-beta (Aβ) and tau PET measurements in Presenilin-1 (PSEN1) E280A mutation carriers from the large Colombian autosomal-dominant Alzheimer's disease (ADAD) kindred. We previously found that mean cortical Aβ and entorhinal cortex (ERC) tau PET measurements begin to increase ∼16 & 6 years, respectively before the kindred's median age at 44 of mild cognitive impairment (Fleisher et al., 2015, Quiroz et al., 2018). Here, we consider the extent to which tau PET measurements in other posterior cerebral regions are related to age, ERC tau, cortical Aβ, and memory performance. Methods: Thirty-six 35±5 year-old cognitively unimpaired kindred members, including 13 PSEN1 mutation carriers and 23 non-carriers, had PiB and flortaucipir (FTP) PET, structural MRI, and CERAD assessment. PiB PET cerebral-to cerebellar DVRs were computed using a large neocortical ROI aggregate (FLR). FTP PET cerebral-to-cerebellar SUVRs were computed in ERC, inferior temporal (IT), inferior parietal (IP), posterior cingulate cortex (PCC), and precuneus (PCu) ROIs. Spearman correlations were used to clarify the extent to which each of the posterior FTP SUVRs relate to age, ERC FTP SUVRs, PiB DVRs, and CERAD memory sub-test scores. Results: Unimpaired mutation carriers were distinguished from non-carriers by higher mean cortical PiB DVRs (p<0.005) and by higher ERC, PCC, and PCu FTP SUVRs (p<0.02). In the unimpaired carriers, mean cortical PiB DVR was associated with higher FTP SUVRs in ERC (r=0.80; p=0.001) and in IT, IP and PCu ROIs (r>0.57; p<0.05); higher ERC and PCu FTP SUVRs were associated with lower CERAD memory scores (r=-0.64; p=0.01 and r=-0.57; p=0.04, respectively); higher mean cortical PiB and higher posterior FTP SUVRs were associated with older age (r>0.62; p<0.02). No such relationships were significant in non-carriers. Conclusions: This study provides new information about the extent to which tau PET measurements in different brain regions are related to age, Aβ burden, and memory performance in the preclinical stages of autosomal dominant AD. Findings also suggest that tau PET measurements may be useful as a biomarker to distinguish individuals at high risk to develop the clinical symptomatology of AD, track disease progression, and evaluate response to disease-modifying treatments.